2001
DOI: 10.1021/jp001024v
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Boehmite Crystallite Size and Steaming on Alumina Properties

Abstract: Boehmite and pseudoboehmite were studied in order to find the effect of their individual properties upon the properties of transitional alumina and R-Al 2 O 3 produced thereof; the influence of steaming on these properties was also considered. Samples were characterized by X-ray powder diffraction, crystalline structure refinement, scanning electron microscopy, thermoanalysis, and nitrogen adsorption. Boehmite and pseudoboehmite had the same crystalline structure but different crystallite dimensions. Differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
49
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 20 publications
9
49
0
4
Order By: Relevance
“…The TG curves became a plateau at temperatures above to 450 • C, suggesting the thermal stability of the samples. A similar trend is observed in the weight loss curves of the sol-gel derived samples indicating the dehydroxylation and crystallization of the solids [34].…”
Section: Thermal Analyses Behaviour Of the As-synthesized Solidssupporting
confidence: 80%
“…The TG curves became a plateau at temperatures above to 450 • C, suggesting the thermal stability of the samples. A similar trend is observed in the weight loss curves of the sol-gel derived samples indicating the dehydroxylation and crystallization of the solids [34].…”
Section: Thermal Analyses Behaviour Of the As-synthesized Solidssupporting
confidence: 80%
“…A similar phenomenon was reported by Hua et al [27] in the case of sulfated alumina-zirconia catalyst. An endothermic peak was also observed for SO 4 2− /Al 2 O 3 -ZrO 2 sample at higher temperatures due to phase transformation of alumina from gamma to alpha as reported in the literature [28]. No significant information was obtained from the TGA/DTA profiles of molybdenum oxide and tungsten oxide-promoted samples.…”
Section: Resultssupporting
confidence: 47%
“…This is in accordance with data from the literature, 30 which showed that the mass loss in pseudoboehmite is higher than the mass loss in boehmite (about 1 wt. %.…”
Section: % Residuesupporting
confidence: 93%